Corruption, capitalism and democracy - Girling, J. L. S. (London ; New York : Routledge, 2002)
This book is an important and very relevant study of corruption which is ever present in political life. Girling demonstrates that corruption does not disappear as countries develop and modernize, but rather that corruption takes on new forms. -- Provided by publisher.
Book Cover; Title; Contents; Preface; Acknowledgements; Introduction; Functional corruption: a developmental role?; Dysfunctional corruption and destabilized politics; Normative strengths; Conclusion: corruption; structural, symbolic; Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Political corruption -- Case studies; Democracy; Capitalism; Corruption (Politique) -- Études de cas; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Capitalism; Democracy; Political corruption; Demokratie; Kapitalismus; Korruption; Democratie; Kapitalisme; Corruptie; Démocratie.; Capitalisme; Corruption; Electronic books; Case studies